2020
DOI: 10.1002/fee.2219
|View full text |Cite
|
Sign up to set email alerts
|

Salvage logging effects on regulating ecosystem services and fuel loads

Abstract: Salvage logging, or logging after natural disturbances such as wildfires, insect outbreaks, and windstorms, is carried out to recover some of a forest's natural and/or economic capital. However, trade‐offs between management objectives and a lack of consensus on the ecological consequences of salvage logging impair science‐based decision making on the management of forests after natural disturbances. We conducted a global meta‐analysis of the impacts of salvage logging on regulating ecosystem services and on f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 62 publications
(24 citation statements)
references
References 51 publications
1
23
0
Order By: Relevance
“…This finding is comparable to previous research, which has illustrated declines in post‐fire sediment erosion associated with the presence of wood and wood mulches (Prats, Gonzalez‐Pelayo, et al, 2019; Robichaud, Lewis, Wagenbrenner, Brown, & Pierson, 2020). However, the longer‐term efficacy of wood for reducing post‐fire hillslope erosion remains uncertain, as Leverkus et al (2020) found that the effect of fine wood (twigs and branches <7.6 cm diameter) on the soil surface had largely disappeared after approximately 5 years. Recent observations from our sites indicated that, in some cases, sediment had filled the storage areas upslope of wood pieces on the salvaged logged sites, suggesting that these pieces will be ineffective at storing additional sediment over the longer‐term.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This finding is comparable to previous research, which has illustrated declines in post‐fire sediment erosion associated with the presence of wood and wood mulches (Prats, Gonzalez‐Pelayo, et al, 2019; Robichaud, Lewis, Wagenbrenner, Brown, & Pierson, 2020). However, the longer‐term efficacy of wood for reducing post‐fire hillslope erosion remains uncertain, as Leverkus et al (2020) found that the effect of fine wood (twigs and branches <7.6 cm diameter) on the soil surface had largely disappeared after approximately 5 years. Recent observations from our sites indicated that, in some cases, sediment had filled the storage areas upslope of wood pieces on the salvaged logged sites, suggesting that these pieces will be ineffective at storing additional sediment over the longer‐term.…”
Section: Discussionmentioning
confidence: 99%
“…Limited research into post‐fire land management strategies has led to continued debate of their potential benefits and trade‐offs (DellaSala et al, 2006; Donato et al, 2006; Leverkus et al, 2020; Leverkus, Puerta‐Pinero, Guzman‐Alvarez, Navarro, & Castro, 2012; McIver & Starr, 2000). For example, the removal of standing and downed large wood may eliminate important structural components that can help facilitate the recovery of terrestrial and aquatic systems (Lindenmayer & Noss, 2006; Maia et al, 2014; May & Gresswell, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…We compiled a global database of species abundances in salvage-logged and unlogged naturally disturbed plots by extending two recent reviews (Fig. 2 ) 6 , 7 . The data compilation followed a systematic review protocol to ensure high quality standards in data selection 39 .…”
Section: Methodsmentioning
confidence: 99%
“…Salvage logging is conducted in all forest types, and is common even in areas that are otherwise excluded from logging, such as national parks 4 . By extracting timber and other tree biomass from large areas 5 , salvage logging can impair ecosystem services 6 and affect the biodiversity of deadwood-dependent species 7 . Salvage logging can have more profound effects on biodiversity than natural disturbance or logging alone due to the additive and interacting effects of the two disturbances 8 , 9 .…”
Section: Introductionmentioning
confidence: 99%
“…Because salvage logging immediately follows the natural disturbance (i.e. up to 3 years), it acts as an additional disturbance (Lindenmayer, McBurney, Blair, Wood, & Banks, 2018; Morissette, Cobb, Brigham, & James, 2002), with possible negative effects on species richness, community recovery of various species groups (Thorn et al, 2018) and ecosystem services (Leverkus et al, 2020).…”
Section: Introductionmentioning
confidence: 99%